Acute Outcomes of Isolated Pneumocephali in Children After Minor Blunt Head Trauma. Issue 9 (September 2018) - Blanchard, Ashley; Cabrera, Keven I.; Kuppermann, Nathan; Dayan, Peter S.
Abstract : Objectives: We aimed to determine the prevalence of and adverse outcomes caused by pneumocephali in children with minor blunt head trauma who had no other intracranial injuries (ie, isolated pneumocephali). Methods: We conducted a secondary analysis of a public use dataset from a multicenter prospective study of pediatric minor head trauma. We included children younger than 18 years with Glasgow Coma Scale (GCS) scores of 14 or 15 and non-trivial mechanisms of injury who had cranial computed tomographies obtained. Patients with isolated pneumocephali were those without other traumatic brain injuries (TBIs) but could have non-depressed or basilar skull fractures (BSFs). We defined adverse outcomes as death, need for neurosurgery, or intubation more than 24 hours for TBI. Results: Pneumocephali occurred in 148 (1.0%; 95% confidence interval, 0.8%–1.2%) of 14, 983 patients; 54 (36.5%) of 148 were isolated. Of these 54 patients, 42 (77.8%) had associated BSFs (7 of whom also had linear skull fractures) and 8 (14.8%) had associated linear skull fractures without BSFs; 4 patients (7.4%) had no fractures. Thirty-three patients (61.1%) had both GCS scores of 15 and no other signs of altered mental status. All patients with isolated pneumocephali and available descriptive data (n = 26) had small-sized pneumocephali. There were no deaths, neurosurgical interventions, or intubations for more than 24 hours for TBI (95% confidence interval for any of the outcomes, 0%–7.9%) in the 54 patients with isolated pneumocephali. Conclusions: Children with isolated pneumocephali and GCS scores of 14 or 15 after minor blunt head trauma are unlikely to have adverse clinical outcomes.